2021
DOI: 10.3390/biology10090860
|View full text |Cite
|
Sign up to set email alerts
|

Pectins and Olive Pectins: From Biotechnology to Human Health

Abstract: Pectins are a component of the complex heteropolysaccharide mixture present in the cell wall of higher plants. Structurally, the pectin backbone includes galacturonic acid to which neutral sugars are attached, resulting in functional regions in which the esterification of residues is crucial. Pectins influence many physiological processes in plants and are used industrially for both food and non-food applications. Pectin-based compounds are also a promising natural source of health-beneficial bioactive molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…It is important to note that neat BPFs exhibit a relatively high antioxidant activity itself, with a 55% inhibition of DPPH• under the experimental conditions used. This fact could be attributed to the antioxidant activity of casein [ 39 ] and pectin [ 48 ]. It has been demonstrated that the presence of aromatic amino acids such as Trp, Tyr and Phe favour the antioxidant activity of peptides and that the indole and pyrrolidine rings in Trp and Pro, respectively, can act as hydrogen donors (via hydroxyl groups) in the deactivation of hydroxyl radicals [ 40 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that neat BPFs exhibit a relatively high antioxidant activity itself, with a 55% inhibition of DPPH• under the experimental conditions used. This fact could be attributed to the antioxidant activity of casein [ 39 ] and pectin [ 48 ]. It has been demonstrated that the presence of aromatic amino acids such as Trp, Tyr and Phe favour the antioxidant activity of peptides and that the indole and pyrrolidine rings in Trp and Pro, respectively, can act as hydrogen donors (via hydroxyl groups) in the deactivation of hydroxyl radicals [ 40 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a polymer with linear structure in which few hundred to thousand galacturonic acid units are linked via α-1,4-glycosidic bond forming the backbone, which can be substituted with other neutral sugars (e.g., rhamnose, galactose, mannose, glucose, and xylose). Methyl esterification of galacturonic acid also occurs [75]. Due to suitable technological (e.g., emulsifying activity and stability) and functional properties (e.g., prebiotic, anti-inflammatory, etc.…”
Section: Pectinsmentioning
confidence: 99%
“…Olive pomace has been described as a rich source of pectins [75,78], with some properties similar to apple pectins, to be applied in the food and pharmaceutical industries [49][50][51]. Nonetheless, olive pomace pectin seems to have a higher degree of methyl-esterification, acetylation, and total neutral sugar content than apple pectin [75]. Extracts rich in phenolic compounds associated with pectins (called pectoliv extracts) have also been recently produced from two-phase olive pomace.…”
Section: Pectinsmentioning
confidence: 99%
“…Conversely, soluble fiber, such as pectin, gums, xyloglucans, inulin, maltodextrins, starch and polydextrose are highly fermentable by bacteria of the large intestine [ 19 ]. Soluble fiber is found in vegetables, whole grains, such as oats and barley, and fruits, in particular, the peels of apples and citrus, which are highly enriched in pectin ( Table 1 [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]).…”
Section: Biological Effects Of Pectinmentioning
confidence: 99%